Landing stability analysis for lunar landers using computer simulation experiments. (21st December 2017) - Liu, Yuanyuan; Song, Shunguang; Li, Ming; Wang, Chunjie
In the overall design and performance prediction of spacecrafts intended to accomplish soft landing on the moon, touchdown dynamics analysis during the landing phase is one of the most important tasks. Due to uncertainties of the landing site and flight states of the vehicle at touchdown, the landing stability is systematically studied in this article by employing the techniques of computer experiments. Firstly, the landing dynamics simulation model of a lunar lander is established and verified by physical tests. Then, design of experiments and response surface methodology have been utilized to analyze the landing stability. Consequently, main effects of initial landing conditions (inputs) on landing dynamics responses (outputs) have been investigated. Response surface models for approximating relationships between inputs and outputs are also acquired. The worst sets of landing conditions and boundaries of initial velocities for stable landings are finally determined with the help of response surface models. The approach for landing stability analysis proposed in this article has been proven effective and efficient and provides valuable guidance for the lander design and analysis.